KONFORMITAS PETANI DALAM USAHATANI KEDELAI (Suatu Kasus di Kecamatan Jatiwaras Kabupaten Tasikmalaya,Provinsi Jawa Barat) - Ivan Sayid Nurahman; Iwan Setiawan; Trisna Insan Noor; Meddy Rachmadi (Universitas Galuh Ciamis, 2019)
Conformity is the pressure to have an attitude or to have behavior in a way that is consistent with rules that show people should behave (Spradley and David, 2012). This study aims to determine the causes of farmers to conform to farmer groups. Then how do the system of values and norms take place within the farmer group so that they can regulate behavior and direct the way of thinking of its members. The results showed that the most dominant factors affecting the behavior of soybean farmers in Jatiwaras Sub-district to conduct conformity included trust and cohesiveness. The high level of trust and the close relationship between individuals (cohesiveness) towards the group raises increasingly high conformity. On the contrary, equality of opinion and agreement are included in the low category so that if there is a difference of opinion on the group agreement there will be a decrease in the level of conformity. The way of thinking and behavior of soybean farmers tends to be based on rationality, so obedience to recommendations and rules in groups is often ignored.